Interaction of BACH2 with FUS promotes malignant progression of glioma cells via the TSLNC8–miR‐10b‐5p–WWC3 pathway. Issue 11 (26th September 2020) - Yang, Yang; Liu, Xiaobai; Zheng, Jian; Xue, Yixue; Liu, Libo; Ma, Jun; Wang, Ping; Yang, Chunqing; Wang, Di; Shao, Lianqi; Ruan, Xuelei; Liu, Yunhui
Abstract : Glioma, a common malignant tumour of the human central nervous system, has poor prognosis and limited treatment options. Dissecting the biological mechanisms underlying glioma pathogenesis can facilitate the development of better therapies. Here, we investigated the endogenous expression of BTB and CNC homolog 2 (BACH2), fused in sarcoma (FUS), TSLNC8 and microRNA (miR)‐10b‐5p in glioma cells and tissues. We studied the interaction between BACH2 and FUS and its contribution to glioma progression. We demonstrated that the interaction between BACH2 and FUS promoted glioma progression via transcriptional inhibition of TSLNC8. Overexpression of TSLNC8 restrained glioma progression by suppressing miR‐10b‐5p. Binding of TSLNC8 to miR‐10b‐5p attenuated the suppression of WWC family member 3 (WWC3) by miR‐10b‐5p and activated the Hippo signalling pathway. Growth of subcutaneous xenografts could be inhibited by knockdown of BACH2 or FUS, by overexpressing TSLNC8 or a combination of the three, also leading to a prolonged survival in nude mice. Our results indicate that the BACH2 and FUS/TSLNC8/miR‐10b‐5p/WWC3 axis is responsible for glioma development and could serve as a potential target for the development of new glioma therapies. Abstract : Interaction of BTB and CNC homolog 2 (BACH2) with fused in sarcoma (FUS) promoted glioma progression via transcriptional inhibition of TSLNC8. Overexpression of TSLNC8 restrained glioma progression by suppressing miR‐10b‐5p. Binding of TSLNC8 to miR‐10b‐5p attenuated the suppression of WWC family member 3 (WWC3) by miR‐10b‐5p and activated the Hippo signalling pathway. BACH2 and FUS/TSLNC8/miR‐10b‐5p/WWC3 axis is responsible for glioma development and could serve as a potential target for glioma therapies.